Is protein structure enough? A review of the role of lipids in SLC6 transporter function. (1st May 2019) - Schumann-Gillett, Alexandra; Blyth, Mitchell T.; O'Mara, Megan L.
Graphical abstract: Highlights: SLC6 symporters share conserved architecture, yet details of their alternating access transport mechanism remain elusive. Studies of SLC6 membrane transporters have focused on transporter structure, rather than their environment. Studies that include diverse environmental lipids could reveal the molecular details of SLC6 substrate transport. Abstract: SLC6 neurotransmitter transporters facilitate the Na + - and Cl − -dependent uptake of amino acids and amino acid derivatives into cells. Disrupting transport leads to a range of neurological disorders. However, the SLC6 substrate transport mechanism is a topic of ongoing debate. Here, we review the prominent SLC6 substrate transport mechanisms through the lens of molecular dynamics simulations. SLC6 transporters are membrane proteins, yet their transport mechanism(s) have largely been studied without considering the impacts of synaptic lipid composition, or endogenous lipid modulators, on transporter structure and function. In this review, we highlight the importance of studying membrane transporters in an appropriate membrane model, and present opportunities for the community to glean understanding and insight into SLC6 transporter structure and function—in particular transport mechanism(s)—when both membrane lipids and endogenous lipid modulators are considered.